Church of war: propaganda and disinformation in Patriarch Kirill’s discourse on Russia’s aggression - Marcin Składanowski; Andrzej Szabaciuk; Agnieszka Łukasik-Turecka (Cogent Arts & Humanities)
The Moscow Patriarchate holds a significant position within the Russian disinformation and propaganda system. Since the onset of the aggression against Ukraine in 2022, Patriarch Kirill (Vladimir Gundyayev) has fervently supported Russian military actions, attributing them with religious and metaphysical significance. This article aims to explore whether Kirill’s public discourse merely echoes the ideas propagated in state propaganda or if the Russian Orthodox Church (ROC) operates as an autonomous entity within the anti-Ukrainian propaganda and disinformation framework. The analysis focuses on the speeches delivered by Kirill as the leader and most important representative of the ROC. Our assertion is that Patriarch Kirill provides religious and theological validation for the official interpretations of the war’s causes, thereby actively engaging in the ideological battle against the West. While the ROC displayed some degree of autonomy in its discourse on the Russo-Ukrainian conflict before 2022, it has since become an integral component of the Russian state’s system of disinformation and propaganda against Ukraine, as well as a broader adversary against the West and the values associated with Western democratic societies.